Catastrophic health expenditure and multimorbidity among older adults in Brazil - Gabriella Marques Bernardes; Helton Saulo; Rodrigo Nobre Fernandez; Maria Fernanda Lima-Costa; Fabíola Bof de Andrade (Universidade de São Paulo, 2020)
ABSTRACT OBJECTIVE: To estimate the relation between catastrophic health expenditure (CHE) and multimorbidity in a national representative sample of the Brazilian population aged 50 year or older. METHODS: This study used data from 8,347 participants of the Estudo Longitudinal de Saúde dos Idosos Brasileiros (ELSI - Brazilian Longitudinal Study of Aging) conducted in 2015-2016. The dependent variable was CHE, defined by the ratio between the health expenses of the adult aged 50 years or older and the household income. The variable of interest was multimorbidity (two or more chronic diseases) and the variable used for stratification was the wealth score. The main analyses were based on multivariate logistic regression. RESULTS: The prevalence of CHE was 17.9% and 7.5%, for expenditures corresponding to 10 and 25% of the household income, respectively. The prevalence of multimorbidity was 63.2%. Multimorbidity showed positive and independent associations with CHE (OR = 1.95, 95%CI 1.67-2.28, and OR = 1.40, 95%CI 1.11-1.76 for expenditures corresponding to 10% and 25%, respectively). Expenditures associated with multimorbidity were higher among those with lower wealth scores. CONCLUSIONS: The results draw attention to the need for an integrated approach of multimorbidity in health services, in order to avoid CHE, particularly among older adults with worse socioeconomic conditions.